1990
DOI: 10.1111/j.1399-6576.1990.tb03100.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes of blood pressure and cerebral arterio‐venous oxygen content differences (AVDo2) with and without bupivacaine scalp infiltration during craniotomy

Abstract: In 20 patients subjected to craniotomy for supratentorial cerebral tumours, the effect of scalp infiltration with bupivacaine before incision was evaluated by measuring mean arterial blood pressure (MABP) and cerebral arterio-venous oxygen content differences (AVDO2) repeatedly during the operation. All patients were given halothane 0.5% anaesthesia. Ten patients were given bupivacaine 0.25% and ten patients were given normal saline for scalp infiltration prior to incision. The study was performed in a double-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…This could be because there was less nociceptive stimulation with intracranial surgical procedures than with abdominal or orthopedic surgery. Moreover, scalp infiltration of a local anesthetic was reported to attenuate the changes in cerebral arteriovenous oxygen content difference and blood pressure by incision in neurosurgery [19]. Bisonnette et al reported that V mca was unchanged during isoflurane anesthesia for 1.5-6 h at 1.0 MAC in children with concomitant epidural local anesthetic [20].…”
Section: Discussionmentioning
confidence: 98%
“…This could be because there was less nociceptive stimulation with intracranial surgical procedures than with abdominal or orthopedic surgery. Moreover, scalp infiltration of a local anesthetic was reported to attenuate the changes in cerebral arteriovenous oxygen content difference and blood pressure by incision in neurosurgery [19]. Bisonnette et al reported that V mca was unchanged during isoflurane anesthesia for 1.5-6 h at 1.0 MAC in children with concomitant epidural local anesthetic [20].…”
Section: Discussionmentioning
confidence: 98%
“…Cette étude a mis en évidence que la PAM montait significativement après incision cutanée dans le groupe sérum salé alors que la fréquence cardiaque restait stable dans les deux groupes. Engberg et al [ 12 ], dans une étude prospective randomisée en double aveugle portant sur 10 malades par groupe, ont montré que l'augmentation de la PAM était significativement plus élevée dans le groupe infiltré par sérum salé par rapport au groupe infiltré par bupivacaine à 0,25% (P< 0.0005). Hillman et al [ 1 ] dans une étude prospective randomisée (21 par groupe) a montré l'efficacité de l'infiltration du scalp par bupivacaine 0,5% mL non adrénalinée avec une dose de 16,4 ± 5ml dans la réduction de la PAM et la Fc après l'incision cutanée en comparaison avec un groupe placebo.…”
Section: Discussionunclassified
“…Anesthesiologists may encounter hemodynamic changes that require pharmacological intervention due to a noxious stimulus resulting from skull pin fixation. Acute arterial hypertension may lead to intracranial hemorrhage and induce intracranial hypertension and cerebral edema in patients with intracranial tumor 2 , 3 . Thus, various strategies such as local anaesthetics, opioids, and scalp blocks have been used to blunt hemodynamic responses induced by skull pin fixation 2 , 4 7 .…”
Section: Introductionmentioning
confidence: 99%